Performance evaluation of GaAs photonic crystal based directional coupler all optical switch - M, Sivasindhu; Samundiswary, P (International Journal of Engineering and Technology, 2018)
In future, the telecommunication systems will be totally based upon the photonic integrated circuits and components for the transmission of optical signals. Since optical signals offer high speed, less delay and higher efficiency. This introduces a new research area for photonic crystal based optical components like optical switch, multiplexer, optical filters etc. Among these devices, the optical switch draws more attention due to its primary switching operation. Hence, this paper deals with the modified design structure of GaAs photonic crystal based directional coupler all optical switch which operates at the wavelength of 1300nm. Further the switching performance evaluation of this device is made for both electro optic effect and non-linear optical effect. The design and simulation of the optical switch is done through Comsol Multiphysics software.Â Â Â